Predicting Ground-Level Enhancement Events and >500 MeV Proton Intensity Using Proton and Electron Observations - Marlon Núñez (Universe)
Ground-Level Enhancements (GLEs) pose a potential hazard for crew and passengers on polar routes. The accurate estimation of the integral proton flux of Solar Energetic Particle (SEP) events is crucial for assessing the expected radiation dose. This paper describes a new approach that predicts the occurrence of GLEs and the associated >500 MeV intensity using proton and electron data. The new approach utilizes the Geostationary Operational Environmental Satellites (GOESs) for proton observations and the Advanced Composition Explorer (ACE) satellite for electron observations. Núñez et al. proposed a GLE occurrence predictor called the High Energy Solar Particle Events foRecastIng and Analysis (HESPERIA) University of Málaga Solar particle Event Predictor (UMASEP-500), which did not include a model for predicting the >500 MeV integral proton intensity. This paper presents a comparison in terms of the GLE event occurrence between the HESPERIA UMASEP-500 and a new approach called UMASEP-500. Although the new approach shows a slightly better critical success index (CSI), which combines the probability of detection (POD) and false alarm ratio (FAR), the difference is not statistically significant. The main advantage of the new UMASEP-500 is its ability to predict the expected >500 MeV proton intensity. This study provides initial insight into a new era of electron and proton telescopes that will be available at L1 in the coming years.